2013
DOI: 10.1063/1.4824022
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid gating reveals trap-filled limit mobility in low temperature amorphous zinc oxide

Abstract: Articles you may be interested inModel for determination of mid-gap states in amorphous metal oxides from thin film transistors Trap states and space charge limited current in dispersion processed zinc oxide thin films Permanent optical doping of amorphous metal oxide semiconductors by deep ultraviolet irradiation at room temperature Appl. Phys. Lett. 96, 222101 (2010); 10.1063/1.3429586 Role of order and disorder on the electronic performances of oxide semiconductor thin film transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…S2(a) †] to evaluate electron transport in a-ZnO thin lms prepared with different surface coverage and morphologies. Recently Bubel et al 53 have shown that a-ZnO exhibits trap-lled limit mobility through an ionic liquid gating method. However all the mobility values presented here are below the trap-lled limit and determined using a conventional bottom-gate TFT architecture.…”
Section: Surface Coverage and Morphology Of A-zno On Ito-coated Glassmentioning
confidence: 99%
“…S2(a) †] to evaluate electron transport in a-ZnO thin lms prepared with different surface coverage and morphologies. Recently Bubel et al 53 have shown that a-ZnO exhibits trap-lled limit mobility through an ionic liquid gating method. However all the mobility values presented here are below the trap-lled limit and determined using a conventional bottom-gate TFT architecture.…”
Section: Surface Coverage and Morphology Of A-zno On Ito-coated Glassmentioning
confidence: 99%
“…We can safely exclude possible effects of contact Schottky barrier on the observed mobility modulation considering the choice of Al electrode that has been shown to form an ohmic contact on TiO x 26,29,33,37,40 and the negligible barrier height lowering effected by gate bias (Supplementary Note 1). The origin of gateinduced mobility modulation has been previously speculated to be related with the sub-bandgap trap states (localized tail states) 41,42 , typically present near the conduction band edge (E c ) of amorphous semiconductors with an exponential decrease in their density of states. Particularly, Lee et al have proposed a power law dependence of the saturation-regime μ FE on V g with the following expression 16,42 :…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of spin‐coated oxide films depends on the speed, acceleration, steps, time, and repetition number of the spinning process and the solution's viscosity and molar concentration. According to previous studies, the minimum achievable film thickness and viscosity range of available inks by spin‐coating are 5 nm and 1–5200 cP, respectively . However, spin‐coating has several disadvantages in terms of the material waste associated with the ink, inapplicability to large‐area or curved substrates, and a low throughput.…”
Section: Fundamentals Of the Solution Processing Technique For Oxide mentioning
confidence: 99%